O kwadratowym modlitewniku Henryka Wańka [rec. Henryk Waniek: Notatnik i modlitewnik drogowy. 1984–1994. Szczecin- Bezrzecze–Szczecin: Wydawnictwo Forma–Dom Kultury 13 Muz, ss. 144.] - Kadłubek, Zbigniew (Śląskie Studia Polonistyczne, 2015)
At the very beginning of his review, the author indicates that Notatnik i modlitewnik drogowy by Henryk Waniek is a remarkably eccentric piece of writing (in accordance with the etymology of this word as located outside centres), placing itself outside dominant discourses and modes. In Waniek’s book artistic competence and talents merge as it also contains some prints by the author. Despite the absolute originality of the title, it has been taken from a certain semantic field of meanings close to Waniek and well known to him from his Silesian peregrinations. Therefore, it can be said that the nomadic prose of this publication is part of the geopoetic trend (the author sees Silesia, sees a road, sees space for its own sake), yet it also remains characteristic of Waniek’s writing in being esoteric, esseistic, reminiscent and metaliterary.